Effects of quality circle participation on employee perception and attitude in five Malaysian companies - Abo-Alhol, Tariq R. A.; Ismail, Md. Yusof; Salit, Mohd Sapuan; Megat Ahmad, Megat Mohamad Hamdan (National Institute of Science Communication and Information Resources, 2006)
This study investigates changes in employee attitude brought about through participation in Quality Circle (QC). Assessment of circle performance was measured by technical aspects, length of participation, training, member feelings about QCs, job satisfaction and job commitment. Study illustrates the impacts of participation on 130 workers from 5 Malaysian companies participated in a survey. Results show that QCs develop positive attitudes among employees who derive job satisfaction when they feel that their companies are a good place to work and consequently, more willing to extend their efforts for their companies.